Analysis of the Translation Approach of Surah Al-Fatihah by the Ministry of Religion of the Republic of Indonesia and M. Quraish Shihab - Surya Ningsih; Andi Abdul Hamzah (al-Afkar, Journal For Islamic Studies, 2026)
This article aims to analyze the translation approaches used in the translation of Surah Al-Fatihah by two parties: the Ministry of Religious Affairs of the Republic of Indonesia in its official translation of the Mushaf Al-Qur’an, and M. Quraish Shihab in his commentary Tafsir al-Mishbah. This study uses a qualitative descriptive-comparative approach to examine the differences and similarities in translation methods, with reference to contextual and textual translation theories. The results show that the Ministry of Religious Affairs uses a more literal approach with limited dynamic elements, while Quraish Shihab tends to apply a communicative and interpretative approach by paying attention to the context of meaning and thematic interpretation.